Antes da República, sob o olhar do Império: a produção do modo de vida e invenção de uma territorialidade diaspórica. O caso de Frutal/Uberaba (MG) - Santos, José Ricardo Marques dos (2018)
This thesis has like a goal investigate the emergence of na área of freedon, the basis of a culture of freedom, as couterculture of na ethnically absolute regional and local identily. If aims to understand how it was possibile to create a conter-narrative created by africans, africans and their descendants in the attempt to aggregte their experiences in Frutal/Uberaba (MG). We investigate all forms of totalization that overlaps the experiences of these subjects – especially the narratives of orign of the cities – that produce cultural damages to theses populations. It is intended to delineate the inventions of meanings, displacements of meaning, the effect of which is the producion of descentralization where oppsitional symbolic forms are recorded. The research consisted by means of documents such as minutes of the municipal councils of Frutal/Uberaba (MG), admnistrative and birth admnistraive inquiries. In addition to researches in the Florestan Fernandes collecion, Minas Public Archives, Public Archive of Uberaba (MG), Public Archive of Frutal (MG). Here we defend the invention of a territoriality of the african diáspora by africans, africans and their descendants as part of the Black Atlantic rhizome.